Comparison of cardio respiratory endurance and Vo, max between professional and Amateur women bharathanatyam dancers - Sabaananth, S.; Gopinath, V. (University of Jaffna, 2011)
The purpose of this study was to compare Cardiorespiratory Endurance (CRE) and Vo, max between Professional and Amateur Bharathanatyam dancers. To achieve the purpose sixty (N=60) women Bharathanatyam dancers were randomly selected and they were classified in to Professional Dancers (PD) (n=30, practice bharathanatyam 90 to 120 min / day for 5 to 6 day / week over the period of minimum 5 years) and Amateur Dancers((AD) (n=30, practice bharathanatyam 30 to 60 min / day/ 2 to 3 day / week over the period of minimum 5 years)) were selected as subjects, their mean age were 17+ 1.3 years, They were measured CRE (Harvard step test) and Vo, max (Queen's step test), the collected data were statistically treated by using independent l' test, 0.05 level of confidence was fixed to test the significance. The result shows that Professional Dancers were better than Amateur Dancers on CRE and VO, max. Hence it was concluded that, professional bharathanatyam dancers developed better CRE and V, max than amateur dancers.
Keywords: CRE; max; professional d ancers; VO; amateur dancers; bharathanatyam